2003
DOI: 10.1291/hypres.26.251
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Regional Variations in Myosin Isoform Shift in Dahl Salt-Sensitive Hypertensive Rats.

Abstract: To evaluate the effects of chronic pressure overload on different parts of the left ventricle (LV), we examined a myosin isoform shift from V1 to V3 as a biochemical marker of LV hypertrophy in Dahl salt-sensitive (DS) rats. Six-week-old DS rats were fed an 8% (high salt, HS; n 24) or a 0.3% (low salt, LS; n 12) NaCl diet. After 2 or 4 weeks, the hearts were dissected and the LVs were separated into four parts (the base and mid- after blood pressure is controlled (12). Studies have confirmed this prominence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…These results suggested that miR‐22 might be partial responsible for PE‐ or Ang II‐induced hypertrophy. As previous reports, besides specific hypertrophic markers, nppa and myh6 also had important roles in mediating cardiac hypertrophy (Sakurai et al, 2003). Considering the effects of miR‐22 on regulating nppa and myh6 expression, we speculated that the effects of miR‐22 in regulating cardiomyocyte hypertrophy might be partially through regulating the expression of nppa and myh6 .…”
Section: Discussionsupporting
confidence: 74%
“…These results suggested that miR‐22 might be partial responsible for PE‐ or Ang II‐induced hypertrophy. As previous reports, besides specific hypertrophic markers, nppa and myh6 also had important roles in mediating cardiac hypertrophy (Sakurai et al, 2003). Considering the effects of miR‐22 on regulating nppa and myh6 expression, we speculated that the effects of miR‐22 in regulating cardiomyocyte hypertrophy might be partially through regulating the expression of nppa and myh6 .…”
Section: Discussionsupporting
confidence: 74%